2013
DOI: 10.1371/journal.pone.0070534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static and Dynamic Stretching on the Diurnal Variations of Jump Performance in Soccer Players

Abstract: PurposeThe present study addressed the lack of data on the effect of different types of stretching on diurnal variations in vertical jump height - i.e., squat-jump (SJ) and countermovement-jump (CMJ). We hypothesized that dynamic stretching could affect the diurnal variations of jump height by producing a greater increase in short-term maximal performance in the morning than the evening through increasing core temperature at this time-of-day.MethodsTwenty male soccer players (age, 18.6±1.3 yrs; height, 174.6±3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 51 publications
4
16
1
1
Order By: Relevance
“…This study confirms previous reports about diurnal variation of short-term maximal performances Chtourou et al 2013b;), performance at SJ and MVC both being significantly higher at 17:00 h than 07:00 h. This variation in short-term maximal performance could be partially explained by similar changes in body temperature (Drust et al 2005;Edwards et al 2005). The present results support this view, oral temperatures being significantly higher at 17:00 h than 07:00 h.…”
Section: Time-of-day Effect In Pre-and Post-training Performancesupporting
confidence: 92%
“…This study confirms previous reports about diurnal variation of short-term maximal performances Chtourou et al 2013b;), performance at SJ and MVC both being significantly higher at 17:00 h than 07:00 h. This variation in short-term maximal performance could be partially explained by similar changes in body temperature (Drust et al 2005;Edwards et al 2005). The present results support this view, oral temperatures being significantly higher at 17:00 h than 07:00 h.…”
Section: Time-of-day Effect In Pre-and Post-training Performancesupporting
confidence: 92%
“…Even though the validity and reliability of T oral are very questionable compared to rectal (Casa et al 2007;Mazerolle et al 2011;Huggins et al 2012), it is still widely used in studies of biological rhythms (Waterhouse et al 2005;Hamouda et al 2012;Chtourou et al 2013). T oral in our study was significantly higher (p < 0.001) in the evening (18:00 h) compared to the morning (08:00 h), with a gain of temperature at rest of 0.6°C.…”
Section: Oral Temperaturecontrasting
confidence: 52%
“…It is believed that dynamic stretching facilitates an increase in flexibility, blood and oxygen flow to the muscles, and a greater increase in body temperature, thus improving conditions for metabolic reactions during activity to potentially improve muscle performance and decrease the occurrence of injury. 4,12 The findings of the current study supports several research articles, as well as the research hypothesis, 3,4,8,[11][12][13][14] however, further research is warranted to test the effects of dynamic stretching on various muscle groups in the body, as well as to specify the mechanism of the aforementioned enhancements.…”
Section: Discussionsupporting
confidence: 86%
“…13 Furthermore, a 2013 report by Amiri-Khorasani et al 10 suggested that dynamic stretching performed prior to activity may induce greater force production due to post-activation potentiation (PAP) and a higher muscle temperature. PAP is related to an increased peak isometric force and the rate of force production; 10 this finding is consistent with a 2014 report which found improved movement times in high school female athletes after dynamic stretching when compared to static stretching.…”
mentioning
confidence: 99%